2017
DOI: 10.1021/acsenergylett.7b01032
|View full text |Cite
|
Sign up to set email alerts
|

Ni–Co Codoping Breaks the Limitation of Single-Metal-Doped IrO2with Higher Oxygen Evolution Reaction Performance and Less Iridium

Abstract: Synthesizing solid solutions of IrO 2 via doping is known to be a viable approach for effectively using iridium metal by enhancing its intrinsic properties. However, such composites at certain fractional values of dopants realize the substitution limit because of lattice mismatch. Here, on the basis of density functional theory studies and experimentation, we demonstrate codoping as an effective approach to overcome this result with an outstanding oxygen evolution reaction (OER) activity. Nickel and cobalt as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 46 publications
3
65
0
Order By: Relevance
“…It is well known that doping heteroatom is another effective method to regulate the electronic structure of active sites . Yang and co‐workers have demonstrated NiCo codoping as an effective approach to enhance intrinsic property for OER of IrO 2 . The study of Krtil and co‐workers indicated that Zn cations substitution into the crystal lattice of RuO 2 leads to the formation of a metastable material, which hinders the formation of surface confined peroxo species and plays an essential role in both oxygen and chlorine evolution reactions .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that doping heteroatom is another effective method to regulate the electronic structure of active sites . Yang and co‐workers have demonstrated NiCo codoping as an effective approach to enhance intrinsic property for OER of IrO 2 . The study of Krtil and co‐workers indicated that Zn cations substitution into the crystal lattice of RuO 2 leads to the formation of a metastable material, which hinders the formation of surface confined peroxo species and plays an essential role in both oxygen and chlorine evolution reactions .…”
Section: Introductionmentioning
confidence: 99%
“…Co is promising candidate among 3d transition metals in terms of its OER electrocatalytic reactivity because its d‐orbital state can offer variable electronic and possibly structural modification to enhance the surface electrocatalysis . Moreover, the coexistence of Co and Ir has been demonstrated to improve the OER activity significantly because of the increased orbital overlap with O 2p and the fluctuation in the electronic density of the IrCo alloy facilitates surface electrode interaction with intermediate adsorbates to result in an optimised surface–oxygen interaction energy. In addition, the role of support materials can affect the whole electrocatalyst system significantly .…”
Section: Resultsmentioning
confidence: 99%
“…However, these catalysts have still not reached the necessary performance. Among fascinating efforts in this area, the rational design of bimetallic compounds of precious metals with earth‐abundant 3d transition metals (e.g., Ni, Co, Fe) was rationalised as wise approach because of the modification of the d‐band electron configuration and absorption energy . Recently, IrM (M=Co, Ni, CoNi) multi‐metallic hollow nanocrystals, synthesised by etching Ir‐based solid nanocrystals were shown to have an excellent activity for the OER and overall water splitting in acid media because of the reduction of the adsorption energy of oxygen intermediates and the favourable hollow feature of the alloy of Ir with 3d transition metals .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Tafel curves for IrO 2 and Ir−Co‐Mn materials. (c) Comparisons of Tafel slopes; Ir mass activity and the overpotential at 10 mA cm −2 for different catalysts (C1 is the Ir0.4/Mn0.6 composite, C2 is IrO 2 /Mn−Co(2 : 1)‐Bir in this work, C3 is INC‐50, C4 is IrNi 0.57 Fe 0.82 , C5 is IrO x /ATO, C6 is Ir 0.54 Co 0.46 O y , and C7 is IrO 2 ‐150). (d) Chronopotentiometric measurements at 100 mA cm −2 .…”
Section: Resultsmentioning
confidence: 99%